Pengaruh Jenis dan Tempo Musik Terhadap Produktivitas Pekerja Bagian Cetak Industri Kue Kering PT. X di Bandung - Oki Mardiawan; Asri Sugiharti (SCHEMA (Journal of Psychological Research), 2011)
The main purpose of this report is to determine whether there is influence of the type and tempo of music on the productivity of an employee while carrying out his job. Two types of music used in this study: classical music and dangdut music. Some employees were divided into 4 groups, each group provided music accompaniment at work, with the type and tempo of music is different, for 30 minutes .After it was seen that the resulting number of cookie cutters. Statistical program ANOVA and t-test was used to analyze the results. In result, it looks kind of music that is very significant effect on productivity is dangdut with fast tempo and classical music with fast tempo. So the kind of classical and dangdut music with fast tempo will affect aspects of existing within the individual that is the attitude, cognitive, and emotional. Where the type and tempo was perceived as a positive stimulation so that the individual is highly motivated then the individual will work with the maximum and this will be seen from the productivity increase as well and vice versa